Analysis of the Impact of the Increase in Value Added Tax (VAT) Rates on the Indonesian People - Adinda Maretsyah Purba; Tasya Alifiya; Ikhwan Rinaldi Lubis; Rizky Ananda Pratama; Hisam Ahyani (ISNU Sumatera Utara, 2025)
The policy of increasing the Value Added Tax (VAT) rate from 10% to 11% as stipulated in the Law on Harmonization of Tax Regulations (HPP Law) has caused various responses among Indonesian people. This tariff change is seen as the government's effort to strengthen state revenues, but on the other hand raises concerns about increasing the economic burden on the community and the potential boost to the rate of inflation. This study aims to analyze the impact of the increase in VAT rates on people's economic conditions and inflation in Indonesia. The research method used is qualitative descriptive with a literature study approach, through the collection of secondary data sourced from books, scientific articles, laws and regulations, and relevant previous research results. The results of the study show that the increase in VAT rates raises pros and cons, especially among business actors and consumers, who consider this policy to have the potential to increase consumption spending. However, based on the provisions of the HPP Law, not all goods and services are subject to VAT, because there are certain criteria and exceptions to maintain people's purchasing power. In addition, the increase in VAT rates has been proven to have no significant influence on inflation in general, because inflation is more predominantly influenced by increases in the prices of strategic commodities such as fuel oil and cooking oil. Thus, the impact of VAT increases on inflation is relatively limited and contextual.